2005
DOI: 10.1103/physreve.71.052901
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of spiral chaos by pulse entrainment in the Aliev-Panfilov model

Abstract: Pulse entrainment between two excitatory media is studied in the Aliev-Panfilov model. We show that a spiral chaos in the continuous excitatory medium can be eliminated by a grid network using the pulse entrainment. This mechanism may be applied to the cardiac system, where the ventricular fibrillation is interpreted as the spiral chaos and the Purkinje fibers act as the grid network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recently, complex and heterogeneous networks of connections among oscillators have been shown to play an important role in physiological processes. A grid network of ventricular fibrillation can eliminate cardiac arrhythmia related to spiral waves in excitable media [4]. Entrainment mediated by direct photic inputs from eyes to the suprachiasmatic nucleus, which adapts mammals' circadian rhythms to periodic daily variation, is dependent on the topology of the connection among circadian oscillating neurons [5].…”
mentioning
confidence: 99%
“…Recently, complex and heterogeneous networks of connections among oscillators have been shown to play an important role in physiological processes. A grid network of ventricular fibrillation can eliminate cardiac arrhythmia related to spiral waves in excitable media [4]. Entrainment mediated by direct photic inputs from eyes to the suprachiasmatic nucleus, which adapts mammals' circadian rhythms to periodic daily variation, is dependent on the topology of the connection among circadian oscillating neurons [5].…”
mentioning
confidence: 99%
“…An alternative method [17] for controlling spiral turbulence that also uses a grid of control points has been demonstrated for the Aliev-Panfilov model. Two layers of excitable media are considered, where the first layer represents the two-dimensional excitable media exhibiting spatiotemporal chaos that is to be controlled, and the second layer is a grid structure also made up of excitable media.…”
Section: A Applying Control Over a Meshmentioning
confidence: 99%
“…Several methods have been proposed for eliminating nonlinear phenomena, including global nonfeedback control [14][15][16][17][18], local nonfeedback control [19][20][21][22][23][24][25][26][27][28][29][30][31][32], global feedback control [33][34][35], and local feedback control [36]. Moreover, numerous studies have shown theoretically and experimentally that waves and patterns can be controlled [37,38].…”
Section: Introductionmentioning
confidence: 99%